Recent advances on the structure identification of components in food - Min Zhao; Jin‐Long Tian (eFood, 2022)
Abstract With the rapid development of food industry, people pay more and more attention to the health benefits of food‐active molecules. The active function of food molecules depends on the chemical structure. So how to determine the chemical composition of food becomes very important. Based on this, this paper mainly expounds the structural analysis methods and specific processes of food chemical components, as well as the difficulties encountered in the determination of structure, and summarizes the latest research trends of food structural analysis. The purpose is to let more scholars understand the structure analysis process of the chemical substance basis of food, and provide a reference for the healthy development of food.